Comparative study of three tests (dye test, indirect haemagglutination test, latex agglutination test) for the detection of antibodies to Toxoplasma gondii in human sera. Issue 2 (February 1982) - Balfour, A H; Fleck, D G; Hughes, H P; Sharp, D
Abstract : An evaluation has been made of a commercial latex agglutination test, Toxotest-MT (TMT) (Eiken, Japan), for the detection of antibodies to Toxoplasma gondii in human sera. In qualitative studies, 878 sera were examined in both the TMT and dye test (DT) and 96.6% agreement was found, In quantitative studies 339 sera were titrated in the TMT and DT, with 337 of these sera also titrated in the indirect haemagglutination test (IHAT). Agreement between the DT and TMT was best, 78% of the sera showing titres within +/- 1 dilution in the two tests. The IHAT and TMT gave 66% agreement, while the DT and IHAT showed least agreement, 40.9%. The results suggest that the pattern of antigenic determinants to which antibody levels are measured are different in the three test systems. The TMT is a better substitute for the DT than the IHAT.